(untitled) (FEATURES AND PROBLEMS OF IMPLEMENTING ECONOMIC REFORMS IN AZERBAIJAN, 2025)
This article examines the basics and application areas of container technologies, especially Docker, in the process of software development. Container technologies are different from traditional virtual machines. Container technologies ensure easy portability of applications and smooth operation in any environment. Docker technology has revolutionized the processes of software development and deployment. Docker technology provides the user with simple architecture and management capabilities. The article examines the advantages and efficiencies of using containers and Docker technologies. The article also provides information about the basic components of Docker. As a result of the study, it was confirmed that containers increase resource efficiency and reduce environment dependency in the modern programming world. Keywords: Docker, container, programming, software development, Docker Hub, Docker Compose, Kubernetes